The actin cytoskeleton - Jockusch, Brigitte M. (Springer, 2020)
Mammalian actins: isoform-specific functions and diseases / Christophe Ampe, Marleen Van Troys -- Assembly and maintenance of myofibrils in striated muscle / Joseph W. Sanger, Jushuo Wang, Yingli Fan, Jennifer White, Lei Mi-Mi, Dipak K. Dube [and others] -- Myosins: domain organisation, motor properties, physiological roles and cellular functions / Thomas A. Masters, John Kendrick-Jones, Folma Buss -- Actin filament structures in migrating cells / Jaakko Lehtimäki, Markku Hakala, Pekka Lappalainen -- Signalling pathways controlling cellular actin organization / Anika Steffen, Theresia E.B. Stradal, Klemens Rottner -- Adp-ribosylation and cross-linking of actin by bacterial protein toxins / Klaus Aktories, Carsten Schwan, Alexander E. Lang -- Common themes in cytoskeletal remodeling by intracellular bacterial effectors / Guy Tran Van Nhieu, Stéphane Romero -- Viruses that exploit actin-based motility for their replication and spread / N. Bishara Marzook, Timothy P. Newsome -- Multiscale view of cytoskeletal mechanoregulation of cell and tissue polarity / Chen Luxenburg, Benjamin Geiger -- Molecular control of actin dynamics in vivo: insights from drosophila / Lena Brüser, Sven Bogdan -- From cytoskeleton to gene expression: actin in the nucleus / Tiina Viita, Maria K. Vartiainen -- What we know and do not know about actin / Thomas D. Pollard.